A 3-D study for Thermal Optimization of Masonry Units - Luísa Costa Sousa (2006)
Masonry is a common building component with good durability and low cost and maintenance. Masonry units should not be considered without taking into account its thermal behavior. The increasing use in Portugal of lightweight concrete masonry blocks demands a study of the topology of these blocks in order to optimize their behavior. The aim of this project is to find an economic single leaf wall easier and quicker to lay with good thermal performance. The work presented here describes a computational method to optimize the topology of lightweight concrete masonry units according to thermal normative requests, where a developed numerical evolutionary algorithm iterates over the direct analysis performed by the commercial code ABAQUS.